Validación de enzimas en la cría y engorde de pollos broilers en época seca en el cantón Salcedo. - Avila Chávez, Edmundo Patricio (2011)
Ecuador, poultry farming is one of the most widely used for the following reasons farms: does not occupy much space and because the cost of meat is low price due to its large feed conversion. Is carried out an investigation in the poultry Avipollo, owned by Mr Patricio Ávila Chávez, located at km 3.5 left out of the way Salcedo - Latacunga, whose geographical location is 57´24´´ 00 ° of South latitude and 78 ° 28´00´´ West longitude, with an altitude of 2955 m, with a duration of 56 days and had as main objective validation of enzymes in breeding and fattening of chicken broilers during dry season. Veg Pro and Ronozyme enzymes and a control treatment were assessed, used a design completely at random (DCA) eight repetitions, 20 birds as an experimental unit giving a total of 480 birds. The parameters that were the subject of study are the following: initial weight, consumption of food (g), gain weight (g), feed conversion, performance to the channel (per cent), mortality (%) and economic treatments analysis. The results were: the enzyme Veg Pro treatment reported the largest gain in the phase of growth (28 days) with 955,23 g. For the fattening (56 days) and total treatment phase enzyme Ronozyme reached the brunt with 1964,44 and 2910,60 g on its agenda. Increased total food consumption was 5995,11 g Ronozyme enzyme therapy. For the variable total feed conversion, witness treatment showed more efficient conversion to 1.46. The enzyme Ronozyme treatment showed the highest percentage to the channel (76,91%). The enzyme Ronozyne treatment shows the higher protein percentage 24.90%. The best relation benefit cost was recorded in the witness with 0.27 treatment